Research on the impact of digital economy development on mineral resource utilization efficiency - Tian, Ye; Chen, Min; Yang, Wu; Wu, Xiaoxuan; Cheng, Manli; Liu, Wei (Frontiers in Earth Science, 2025)
The international geopolitical crisis and the rigid management system increase the risk of a mineral crisis in China, but the development of the digital economy provides a possibility for the efficient utilization of mineral resources. Based on the panel data of 30 provinces (autonomous regions and municipalities) from 2011 to 2022, this research measures the level of China’s digital economy development and the utilization efficiency of mineral resources, and examines the transmission path of the digital economy development on the utilization efficiency of mineral resources by using the mediation effect model. The results show that (1) the development of the digital economy can significantly improve the utilization efficiency of mineral resources, and this conclusion is still valid after the instrumental variables method and other robustness tests. For every unit of progress in the development of the digital economy, mineral resource efficiency improves by 0.226. (2) The upgrading of industrial structure and technological progress play a mediating role in the digital economy and the improvement of mineral resource utilization efficiency. (3) The digital economy has a significant heterogeneous effect on the utilization efficiency of mineral resources in China’s eastern, central, and western regions, with the most prominent positive effect in the central and western regions. The positive effect is most prominent in the Midwest at 0.180, and is not significant in the East.